Foreword to the special issue “feminist approaches to justice: contributions to CSW66” - Joseph, Janice 19XX- (International journal of comparative and applied criminal justice, 2023)
The COVID-19 pandemic and its aftermath have affected the lives and livelihoods of women around the world and their economic impacts are having a regressive effect on gender equality (Madgavkar et al., 2020). Consequently, the gender gap between men and women that has been amplified by the pandemic is not expected to close for another 136 years (Armstrong, 2021). As President of the World Society of Victimology, I am pleased to provide this forward to the special issue. The World Society of Victimology is dedicated to improving the plight of victims of crime and the abuse of power around the globe. These issues are linked to the global fight for gender equality.